2012
DOI: 10.1159/000339262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Medical Nutrition Therapy on Body Fat and Metabolic Syndrome Components in Premenopausal Overweight Women

Abstract: Background/Aims: To evaluate the effects of medical nutrition therapy (MNT) on body composition and metabolic syndrome (MetS) components in premenopausal Korean women with a body mass index ≥23. Methods: Participants (n = 160) were classified into MetS (n = 44) or non-MetS (n = 116) groups based on the criteria proposed by the revised National Cholesterol Education Program-Adult Treatment Panel III and the International Diabetes Federation classification. Anthropometric and dietary assessments and blood analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
0
1
0
2
Order By: Relevance
“…El tamaño muestral se obtuvo utilizando el programa STATA 12.0 y fundamentado en los resultados de un estudio similar cuyo desenlace principal es el cambio en la circunferencia abdominal (15) . Para un nivel de significancia de 5% y una potencia de 80%, el tamaño muestral mínimo requerido es de 20 pacientes por grupo, considerando un abandono de un 50% en cada grupo se seleccionarán 40 mujeres en cada grupo.…”
Section: Tamaño De La Muestraunclassified
See 1 more Smart Citation
“…El tamaño muestral se obtuvo utilizando el programa STATA 12.0 y fundamentado en los resultados de un estudio similar cuyo desenlace principal es el cambio en la circunferencia abdominal (15) . Para un nivel de significancia de 5% y una potencia de 80%, el tamaño muestral mínimo requerido es de 20 pacientes por grupo, considerando un abandono de un 50% en cada grupo se seleccionarán 40 mujeres en cada grupo.…”
Section: Tamaño De La Muestraunclassified
“…El objetivo principal de este estudio es determinar el efecto de Intervención de Enfermería basada en el autocuidado dirigida a mejorar los factores clínicos del SM (obesidad abdominal e hipertensión arterial) y calidad de vida relacionada con salud en mujeres en etapa de climaterio, mediante un estudio cuasi experimental, con grupo control no equivalente (15) durante 12 semanas.…”
Section: Introductionunclassified
“…Excessive weight is a major risk factor for a range of preventable diseases, such as cardiovascular disease, cancer, osteoarthritis, and diabetes [15]. Moreover, the health risks associated with an unbalanced diet have become the leading factor contributing to the global burden of disease as 11 of the top 20 risk factors for the burden of disease are related to diet or physical inactivity [16]. A recent study [17] among adults from 195 countries between the years 1990 and 2017 found that 11 million deaths were attributable to dietary risk factors.…”
Section: Introductionmentioning
confidence: 99%